The phylogeny of Salix revealed by whole genome re-sequencing suggests different sex-determination systems in major groups of the genus. (23rd March 2022) - Gulyaev, Sergey; Cai, Xin-Jie; Guo, Fei-Yi; Kikuchi, Satoshi; Applequist, Wendy L; Zhang, Zhi-Xiang; Hörandl, Elvira; He, Li
Abstract: Background and Aims: The largest genus of Salicaceae sensu lato, Salix, has been shown to consist of two main clades: clade Salix, in which species have XY sex-determination systems (SDSs) on chromosome 7, and clade Vetrix including species with ZW SDSs on chromosome 15. Here, we test the utility of whole genome re-sequencing (WGR) for phylogenomic reconstructions of willows to infer changes between different SDSs. Methods: We used more than 1 TB of WGR data from 70 Salix taxa to ascertain single nucleotide polymorphisms on the autosomes, the sex-linked regions (SLRs) and the chloroplast genomes, for phylogenetic and species tree analyses. To avoid bias, we chose reference genomes from both groups, Salix dunnii from clade Salix and S. purpurea from clade Vetrix . Key Results: Two main largely congruent groups were recovered: the paraphyletic Salix grade and the Vetrix clade. The autosome dataset trees resolved four subclades (C1–C4) in Vetrix . C1 and C2 comprise species from the Hengduan Mountains and adjacent areas and from Eurasia, respectively. Section Longifoliae (C3) grouped within the Vetrix clade but fell into the Salix clade in trees based on the chloroplast dataset analysis. Salix triandra from Eurasia (C4) was revealed as sister to the remaining species of clade Vetrix . In Salix, the polyploid group C5 is paraphyletic to clade Vetrix and subclade C6 is consistent with Argus's subgenus Protitea . Chloroplast datasets separated both Vetrix and Salix as monophyletic, and yielded C5 embedded within Salix . Using only diploid species, both the SLR and autosomal datasets yielded trees with Vetrix and Salix as well-supported clades. Conclusion: WGR data are useful for phylogenomic analyses of willows. The different SDSs may contribute to the isolation of the two major groups, but the reproductive barrier between them needs to be studied.